The role of spatial planning in strengthening human settlement resilience to nature-induced disasters in Chimanimani District, Zimbabwe - Morgen Zivhave; Kudzai Chatiza; Tendai Edith Bvuma; Willoughby Zimunya; Godfrey Musvoto (Discover Sustainability)
Abstract The effectiveness of spatial planning in guiding human settlements has come under scrutiny with the increasing occurrence and severity of climate-induced disasters. This study interrogates the role of spatial planning in promoting resilient settlements in growth points and rural service centres, often overlooked in favour of towns and large cities. Our study adopted mixed methods research and collected quantitative data from 1,161 households from the eight wards most affected by Cyclone Idai in Chimanimani District. We also collected qualitative data from key informants from Chimanimani District and the national government institutions. Findings show that the Chimanimani Rural District Council and the District Coordinator’s office have institutional, technical, and capacity gaps to mobilise actors and guide spatial planning for resilient settlement in response to climate change-induced disasters. The district institutions are stifled by the direct planning and implementation of projects by the national government which bypasses and duplicates local efforts. The rigid spatial planning standards, the flouting of planning guidelines, the parcelling of land by the traditional leadership, and political interference contribute to poor district spatial planning for resilient human settlements. This study recommends an integrated development planning approach that coordinates stakeholders to develop resilient infrastructure for guiding sustainable human settlements.